Peran Profitabilitas pada Pengaruh Struktur Modal terhadap Nilai Perusahaan Sektor Teknologi - Made Ratih Nurmalasari; Putu Diah Kumalasari; Putu Lyra Windyana Putri (Penerbit Goodwood, 2025)
Purpose: This study is designed to analyze the impact of capital structure on firm value in the technology sector and the moderating role of profitability in this relationship. Methodology: A quantitative methodology is utilized in this research. The population in this study consists of all financial statements from technology companies during the period of 2021-2023. The sample in this study consists of 11 companies, with the sample being chosen using a purposeful sampling technique. The data analysis techniques utilized are multiple regression and Moderate Regression Analysis (MRA). Results: (1) Firm value is not impacted by capital structure, and (2) Profitability can strengthen the effect of capital structure on firm value. Conclusions: Capital structure does not have a significant effect on firm value in technology sector companies listed on the IDX during 2021–2023. However, profitability is proven to strengthen the influence of capital structure on firm value. Limitations: A limitation of this study is that it only examines a specific period, which may not fully capture the long-term effects of capital structure and profitability on firm value, especially in a rapidly changing industry like technology. The findings may be influenced by short-term market conditions and may not be applicable to different economic cycles or future trends. Contribution: This study provides valuable insights into the intricate relationship between capital structure, profitability, and firm value, particularly in the rapidly growing technology sector.